Generalization of TOPSIS for Neutrosophic Hypersoft set using Accuracy Function and its Application - Muhammad Saqlain; Muhammad Saeed; Muhammad Rayees Ahmad; F. Smarandache (Neutrosophic Sets and Systems, 2019)
The purpose of MCDM is to determine the best option amongst all the probable options. Due to linguistic assessments, the traditional crisp techniques are not good to solve MCDM problems. This paper deals with the generalization of TOPSIS for neutrosophic hypersoft set primarily based issues explained in section 3. In section 4, the proposed technique is implemented. The proposed technique is easy to implement, and precise and sensible for fixing the MCDM problem with multiple-valued neutrosophic data. In the end, the applicability of the developed method, the problem of parking on which decision maker has normally vague and imprecise knowledge is used. It seems that the outcomes of these examinations are terrific.